Kualitas Batugamping Gorontalo Sebagai Reservoir Air Tanah Berdasarkan Analisis Jenis Porositas - Aang Panji Permana; Sunarty Suly Eraku (EnviroScienteae, 2020)
The potential of limestone in Gorontalo City is not only the use of industrial minerals but also its availability as a reservoir of groundwater reservoirs. The availability of groundwater is the main focus in preserving the environment. For this reason, this research focuses on the quality of limestone reservoirs by analyzing limestone porosity. The purpose of this study was to determine the average porosity percentage, porosity type and porosity quality both semi-quantitative and qualitative. In order to achieve these objectives, two methods are used namely the field survey method and petrographic analysis. The results showed the average percentage of porosity quality of limestone as a reservoir of groundwater in the excellent category with the type of porosity is fracturing and growing (vugular).